Technical efficiency in the portuguese banking sector: a non-parametric approach - Canhoto, Ana (1996)
A striking feature of nowadays Portuguese banking industry is the coexistence of two generations of institutions with considerably different historical backgrounds: old institutions, some of which date back to the nineteenth century, and new institutions operating in Portugal since the 1980s liberalization wave. This paper uses a non-parametric frontier approach to measure technical efficiency in a representative sample of banks, particularly on the contrast detected in the efficiency performance of these two groups. The sample’s returns to scale characterization are also presented, and statistical tests are conducted investigating the relationship between size, age, and efficiency measures.